First Records of Established Populations of Ixodes scapularis (Acari: Ixodidae) Collected From Three Nebraska Counties. Issue 3 (27th November 2019) - Nielsen, Lindsey E; Cortinas, Roberto; Fey, Paul D; Iwen, Peter C; Nielsen, David H
Abstract: Reported cases of Lyme disease in Nebraska have been assumed to be imported from other endemic areas. Previous surveillance efforts provided no evidence of established populations as only individual specimens of Ixodes scapularis (Say) had been collected. In the winter of 2018, adult I. scapularis were found on a dog at Two Rivers State Recreation Area, Douglas County, prompting tick collection at the site and nearby natural areas. In May 2019, all life stages of host-seeking I. scapularis were collected using dragging and flagging techniques in sites located near the Platte River in Douglas, Sarpy, and Saunders counties. This is the first documentation of established populations of I. scapularis in Nebraska.